2013
DOI: 10.6065/apem.2013.18.3.135
|View full text |Cite
|
Sign up to set email alerts
|

Depression and self-concept in girls with perception of pubertal onset

Abstract: PurposeEarly pubertal timing in girls is associated with psychological and behavioral problems. This study aimed to evaluate the psychological features of girls who perceived breast development beginning by analyzing their depression levels and self-concept.MethodsFrom March 2007 to December 2012, 93 girls were enrolled and assigned to a pre-8 (younger than 8 years, n=43) or post-8 (8 years and older, n=50) group according to the age at onset of perceived breast development, and their height, body weight, body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…15 In a similar finding, it was noted that early-maturing Korean girls did not manifest higher levels of depression or lower selfesteem. 16 By contrast, in our previous report we found that self-rated sexual maturity status was related to adolescent psychological well-being regarding self-esteem and interpersonal relationships. 17 The inconsistent results may be due to methodological differences in defining pubertal status.…”
Section: Introductioncontrasting
confidence: 68%
“…15 In a similar finding, it was noted that early-maturing Korean girls did not manifest higher levels of depression or lower selfesteem. 16 By contrast, in our previous report we found that self-rated sexual maturity status was related to adolescent psychological well-being regarding self-esteem and interpersonal relationships. 17 The inconsistent results may be due to methodological differences in defining pubertal status.…”
Section: Introductioncontrasting
confidence: 68%
“…It typically represent adolescent mental health-related investigations, including "headaches, " "dizziness, " "loneliness, " "depression, " "worriedness, " "feeling like hurting others, " "feeling like arguing with others, " "feeling like screaming, " "insomnia, " "waking up early, " "light sleeping, " "muscle pain, " "feeling numb, " "feeling like something is stuck in your throat, " "feeling weak, " and "having suicidal feelings" (24). This scale has been extensively applied in research on depression and psychological well-being in this local setting (25)(26)(27). A 5point Likert scale was applied to rate these items, and all the item scores were added together to create a score representing depressive symptomatology (Cronbach α = 0.844).…”
Section: Outcome Variablesmentioning
confidence: 99%
“…Central precocious puberty (CPP) is caused by the premature activation of the hypothalamic gonadotropin-releasing hormone (GnRH) pulse generator and is generally idiopathic 2) . CPP can be associated with diverse problems such as compromised final adult height and psychological as well as emotional conflicts 3 4 5) . Therefore, an early diagnosis and a proper management are critical 6 7) .…”
Section: Introductionmentioning
confidence: 99%